A Picture Of Anxiety In Preparedness For Death In The Elderly - Adeline Rizky Nathania Putri; Karina M. Brahmana (Indonesian Journal on Education (IJoEd), 2026)
This study aims to determine the characteristics of anxiety in preparing for death in the elderly. Based on the results of the study and data analysis on the characteristics of anxiety in preparing for death in the elderly, several conclusions can be drawn as follows: Both subjects showed a relatively low level of anxiety about death. Although both were aware that they were getting older and their physical condition was declining, death was not seen as something frightening. Death was interpreted more as part of God's will and a natural process of life, so that the anxiety that arose was mild and still well managed. Religiosity was a major factor in preparing for death. Both subjects showed a strong belief in God, which was reflected in their attitude of prayer, surrender, and understanding death as God's will. Spirituality helped them manage their fear, foster a sense of calm, and increase their emotional and mental readiness to face death